2010
DOI: 10.1108/02656711011075116
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the ISO 9001 internal audit to business performance

Abstract: Purpose -The purpose of this paper is to investigate how the internal audit can contribute to an improvement in business performance. The goal is to develop a theoretical model of the integration of quality management systems (QMS) and an internal audit within a broader managerial system and performance reviews of the company. Design/methodology/approach -A theoretical framework was developed for assessing the internal audit's contribution to the achievement of business goals. Based on the theoretically explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 27 publications
2
34
0
5
Order By: Relevance
“…The dimension of this variable is covering the customers feedback, processing performance and products compliance, and SMM performance improvement. The indicator of each dimension of the variable of Internal Audit Contribution has been adopted from the questionnaires provided in the research of Alic & Rusjan (2010). Latent Variable (exogen) has used the term 'PIA' within the diagram path which has been constructing 8 (eight) indicators.…”
Section: Internal Audit Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimension of this variable is covering the customers feedback, processing performance and products compliance, and SMM performance improvement. The indicator of each dimension of the variable of Internal Audit Contribution has been adopted from the questionnaires provided in the research of Alic & Rusjan (2010). Latent Variable (exogen) has used the term 'PIA' within the diagram path which has been constructing 8 (eight) indicators.…”
Section: Internal Audit Contributionmentioning
confidence: 99%
“…Research done by Alic and Rusjan (2010) has demonstrated that the internal audit function is to perform an inspection and evaluation upon the compliance and efficacy of the policy and procedures of the internal controlling system. The positive effects identified upon the QMS can be used as the fundamental evaluation of the internal audit refers to the achievement of the company goal and the development of the company performance.…”
Section: Introductionmentioning
confidence: 99%
“…The model proposes that the independent variable (FA) influences the mediator (IA), which then will influence the dependent variable (CGM). As opined by [63], IA can be examined through its responsibility to ensure business transparency, examining and monitoring effectiveness of internal control and maintain high integrity in their corporate business activities and operations. FA is proposed as the independent variable based on the fact of literature and previous research, which reveals that FA can have strong influence on CGM [1,18].…”
Section: Mediating Propositionmentioning
confidence: 99%
“…Jones et al (1997) found that companies who sought certification because of internal motives, either with or without additional external motives, were more likely to perceive benefits from certification. Several others also reported a stronger influence on certification benefits from internal motives than external motives (Sampaio et al, 2009;Terziovski and Power, 2007;Alic and Rusjan, 2010;Jang and Lin, 2008).…”
mentioning
confidence: 99%